Dose-dependent INhibitory effect of rosuVastatin In Japanese patienTs with Acute myocardial infarcTION on serum concentration of matrix metalloproteinases – INVITATION trial. Issue 4 (October 2018) - Fujisue, Koichiro; Shirakawa, Takuhiro; Nakamura, Shinichi; Yamamoto, Nobuyasu; Oshima, Shuichi; Matsumura, Toshiyuki; Tsunoda, Ryusuke; Hirai, Nobutaka; Tayama, Shinji; Nakamura, Natsuki; Hirose, Toyoki; Maruyama, Hideki; et al.
Highlights: Dose-dependency of rosuvastatin on anti-inflammatory effect is controversial. INVITATION will evaluate dose-dependent anti-inflammatory effect of rosuvastatin. The potential of post-infarcted anti-inflammatory pharmacotherapy will be provided. Abstract: Background: Acute myocardial infarction (AMI) is mainly characterized by the rupture of lipid-rich vulnerable atherosclerotic plaque. The matrix metalloproteinases (MMPs) have been shown to play a critical role in inflammatory processes underlying plaque rupture. Some reports suggested statins inhibit the increased MMP levels after AMI. However, there are a few comparison studies between the different dosages of the same statin and circulating levels of MMPs. Purpose: This study will preliminarily investigate the potential effects of appropriate or low dose of rosuvastatin on circulating MMPs levels in AMI patients. Moreover, we will also obtain plasma from patients while undergoing diagnostic angiography to determine differences in various cardiac sites and peripheral vessels. Methods: This study is a multicenter, open-label, randomized, parallel-group study to be conducted to compare the appropriate or low dose of rosuvastatin in the effect on serum levels of inflammatory markers in AMI patients. The eligible patients undergoing percutaneous coronary intervention (PCI) will be randomly assigned to receive either appropriate or low-dose rosuvastatin daily using a web-based randomization software within 24 h after PCI. The low-dose group will be treated with rosuvastatin 2.5 mg once daily with a follow-up. The appropriate-dose group will begin treatment with rosuvastatin 5 mg once daily, and the dose of rosuvastatin will be titrated to 10 mg within 4 weeks. During administration of the study treatment, subjects will undergo laboratory testing including MMPs and be monitored for the occurrence of adverse events up to 24 weeks. The primary endpoint will be the change rate of MMPs at 24 weeks after administration. Conclusions: INVITATION will compare the appropriate or low dose of rosuvastatin in the effects on serum levels of inflammatory markers including MMPs in AMI patients. This study will provide significant information on rosuvastatin as an anti-inflammatory agent for AMI.